Slow and steady-small, but insufficient, changes in food and drink availability after four years of implementing a healthy food policy in New Zealand hospitals - Mackay S; Rosin M; Kidd B; Gerritsen S; Shen S; Jiang Y; Te Morenga L; Ni Mhurchu C (BioMed Central Ltd, 2024)
BACKGROUND: A voluntary National Healthy Food and Drink Policy (the Policy) was introduced in public hospitals in New Zealand in 2016. This study assessed the changes in implementation of the Policy and its impact on providing healthier food and drinks for staff and visitors in four district health boards between 1 and 5 years after the initial Policy introduction. METHODS: Repeat, cross-sectional audits were undertaken at the same eight sites in four district health boards between April and August 2017 and again between January and September 2021. In 2017, there were 74 retail settings audited (and 99 in 2021), comprising 27 (34 in 2021) serviced food outlets and 47 (65 in 2021) vending machines. The Policy's traffic light criteria were used to classify 2652 items in 2017 and 3928 items in 2021. The primary outcome was alignment with the Policy guidance on the proportions of red, amber and green foods and drinks (≥ 55% green 'healthy' items and 0% red 'unhealthy' items). RESULTS: The distribution of the classification of items as red, amber and green changed from 2017 to 2021 (p < 0.001) overall and in serviced food outlets (p < 0.001) and vending machines (p < 0.001). In 2021, green items were a higher proportion of available items (20.7%, n = 815) compared to 2017 (14.0%, n = 371), as were amber items (49.8%, n = 1957) compared to 2017 (29.2%, n = 775). Fewer items were classified as red in 2021 (29.4%, n = 1156) than in 2017 (56.8%, n = 1506). Mixed dishes were the most prevalent green items in both years, representing 11.4% (n = 446) of all items in 2021 and 5.5% (n = 145) in 2017. Fewer red packaged snacks (11.6%, n = 457 vs 22.5%, n = 598) and red cold drinks (5.2%, n = 205 vs 12.5%, n = 331) were available in 2021 compared to 2017. However, at either time, no organisation or setting met the criteria for alignment with the Policy (≥ 55% green items, 0% red items). CONCLUSIONS: Introduction of the Policy improved the relative healthiness of food and drinks available, but the proportion of red items remained high. More dedicated support is required to fully implement the Policy.
Keywords: Audit; Employees; Food environment; Healthy food policy; Hospital; Nutrition policy; Voluntary; New Zealand; Cross-Sectional Studies; Humans; Nutrition Policy; Beverages; Food Supply; Food Service, Hospital; Hospitals; Food Dispensers, Automatic; Diet, Healthy